Interpretability of machine intelligence in medical image computing and multimodal learning for clinical decision support : second International Workshop, iMIMIC 2019, and 9th International Workshop, ML-CDS 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 17, 2019, Proceedings /: second International Workshop, iMIMIC 2019, and 9th International Workshop, ML-CDS 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 17, 2019, Proceedings. (2019) - Unknown
No abstract available